Analysis of the Quality of Employee Performance on Customer Decision-Making on Bank Syariah Indonesia Murabahah Financing - Eva Zulyani; Ahmad Fauzul Hakim; Nurul Asyimi; Afriani Afriani (LPPM UIKA Bogor, 2023)
This study aims to determine the effect of service quality on customer decisions at Indonesian Sharia Banks in the city of Lhokseumawe. The sampling technique used was purposive sampling technique. The number of samples is 100 people in the city of Lhokseumawe. Research data were analyzed using PLS-SEM (Partial Least Square – Structural Equation Modeling) with SmartPLS 3 software. The results showed that service quality of compliance, assurance, reliability, physical evidence, empathy, and responsiveness had a positive effect on customer decisions of Indonesian Sharia Commercial Banks in the city of Lhokseumawe. Only two variables had a positive and significant effect, namely compliance and responsiveness, the remaining four variables, namely assurance, reliability, tangibles, and empathy, had a positive but not significant effect. The implication of this research is to focus on compliance, assurance, reliability, physical evidence, empathy, and responsiveness which can influence customer decisions at Bank Syariah Indonesia in the city of Lhokseumawe.